Forward Guidance in a Simple Model with a Zero Lower Bound - Gerhard Illing; Thomas Siemsen (Center for Economic Studies and ifo Institute (CESifo), 2014)
In this paper we present a three period setup to model central bank forward guidance in a liquidity trap. We analyze the role of long-run and short-run price stickiness under discretion and commitment in a straightforward and intuitive way. Despite the impact of price rigidity on welfare being non-linear, losses under discretion are lowest with perfectly flexible prices. We show why the zero lower bound may still be binding even long after the shock has gone and characterize conditions when a commitment to hold nominal rates at zero for an extended period is optimal. We then introduce government spending and show that under persistently low policy rates optimal government spending becomes more front-loaded, while procyclical austerity fares worse than discretionary government spending.
Keywords: E43; E52; E58; 330; zero lower bound; forward guidance; commitment; optimal policy